TCP-friendly layered multicast protocol for multimedia streaming - Ghazali, Osman; Hassan, Suhaidi (IEEE Computer Society, 2008)
Layered multicast protocol (LMP) is designed to support simultaneous and real-time multimedia content distribution to large number ofdisparate receivers across the heterogeneous Internet. However, the current layered multicast protocols (LMPs) use the techniques that do not correctly model TCP behaviour, which results in the protocols can't fairly compete with TCP. TCP-friendly layered multicast protocol (TjLMP) is designed to solve the problems with the current LMPs. It use the techniques that closely model TCP behaviour, i.e. scalable RTT estimation and 2-step loss event rate filtering. The techniques enable TjLMP to compete with TCP and get fair amount ofbandwidth share. TjLMP is evaluated using ns2 simulation and the results are compared with the other LMPs.